Perbandingan Hasil Belajar Fisika Siswa Terhadap Metode Pembelajaran Guru Pada Kelas X - Hermansyah, Hermansyah; Maslinda, Maslinda; Anggraeni, Wulan; Haris, Andi; Safitri, Ade (Journal of Science Instruction and Technology, 2023)
This research aims to determine the comparison of student learning outcomes with teacher learning methods in class x SMA Plus Aisyah. This type of research is quasi-experimental. The sampling technique used was probability sampling with a purposive sampling model. The research was carried out in classes X MIA1 and X MIA2 as experimental classes with a total of 22 students in each class. Data collection techniques use documentation, tests and observation. Data analysis used the Wilcoxon test with a significance level of 0.05. The results of the research are that the learning outcomes for class X MIA1 are lower than those for class X MIA2 based on. The conclusion of this research is that teachers' teaching methods influence student grades. The suggestion from this research is that teachers should use video media to foster students' interest in learning.